Dopamine-deprived striatal GABAergic interneurons burst and generate repetitive gigantic IPSCs in medium spiny neurons - Dehorter, Nathalie; Guigoni, Celine; Lopez, Catherine; Hirsch, June; Eusebio, Alexandre; Ben-Ari, Yehezkel; Hammond, Constance (The Journal of neuroscience, 2009)
Striatal GABAergic microcircuits modulate cortical responses and movement execution in part by controlling the activity of medium spiny neurons (MSNs). How this is altered by chronic dopamine depletion, such as in Parkinson's disease, is not presently understood. We now report that, in dopamine-depleted slices of the striatum, MSNs generate giant spontaneous postsynaptic GABAergic currents (single or in bursts at 60 Hz) interspersed with silent episodes, rather than the continuous, low-frequency GABAergic drive (5 Hz) observed in control MSNs. This shift was observed in one-half of the MSN population, including both "D(1)-negative" and "D(1)-positive" MSNs. Single GABA and NMDA channel recordings revealed that the resting membrane potential and reversal potential of GABA were similar in control and dopamine-depleted MSNs, and depolarizing, but not excitatory, actions of GABA were observed. Glutamatergic and cholinergic antagonists did not block the GABAergic oscillations, suggesting that they were generated by GABAergic neurons. In support of this, cell-attached recordings revealed that a subpopulation of intrastriatal GABAergic interneurons generated bursts of spikes in dopamine-deprived conditions. This subpopulation included low-threshold spike interneurons but not fast-spiking interneurons, cholinergic interneurons, or MSNs. Therefore, a population of local GABAergic interneurons shifts from tonic to oscillatory mode when dopamine deprived and gives rise to spontaneous repetitive giant GABAergic currents in one-half the MSNs. We suggest that this may in turn alter integration of cortical signals by MSNs.